Xenophobia in Media: Reconstruction of Subjectivity in Iqbal Al-Qazwini’s Zubaida’s Window - Mahshid Namjoo; Leila Baradaran Jamili; Negar Sharif (Critical Literary Studies)
The present study argues the relationship between the media’s power and the reconstruction of subjectivity in Zubaida’s Window, a novel by Iqbal Al-Qazwini. It is a description of the tortured psyche of the exiled woman and her attempts to reconstruct her displaced subjectivity among different versions of media’s Baudrillardian simulacra and to distinguish reality from unreality. Media’s depictions of death and war’s destruction can generate xenophobia among natives who may blame immigrants for their social problems and disturbing spatial harmony. Qazwini re-emphasizes that xenophobia can destroy an immigrant’s self-perception and trigger the preference for death. Moreover, the hyperreal versions of truth and ignoring the subaltern’s voice and revelation affect an immigrant’s mentality negatively and persuade her/him to prefer loneliness and death to have social interactions. This article focuses on the significance of media in the reconstruction of subjectivity, intensification of anti-immigration views, and the dark sides of modern war based on the interrelated theories of David Miller and Derek Gregory. Considering the issues of compulsory displacement and territoriality, Miller focuses on the ethical/political dimensions, while Gregory examines the causes of armed conflicts and geopolitical factors. By applying such an interdisciplinary approach, the researchers investigate Zubaida’s mental downfall, her failure in the reconstruction of subjectivity, and her inability to reconcile different self-images. This article examines her ceaseless effort to reverse the colonial power of media by adhering to her homeland’s memories, or watching her country’s news through TV’s representation, or ignoring spatial interactions, and lack of interest in self-renovation.